Transport Mechanism of Anthracycline Derivatives in Rat Polymorphonuclear Leukocytes : Effect of Sodium Fluoride on Pirarubicin Uptake - KITAZAWA, Fumiaki; YOKOYAMA, Teruyoshi; NAGASAWA, Kazuki; NOMIYAMA, Masako; TSUMURA, Akiko; OHNISHI, Noriaki (Biological & pharmaceutical bulletin, 1995)
We previously revealed that pirarubicin (THP) was actively taken up by rat polymorphonuclear leukocytes via a carrier-mediated transport system. In the experiment on the effects of the metabolic inhibitors, rotenone, 2, 4-dinitrophenol and sodium cyanide significantly decreased the THP transport. However, sodium fluoride (NaF) significantly increased the uptake, and this result is different from that in some reports. Therefore, we examined the action of NaF on THP uptake by the leukocytes to clarify the discrepancy in the effect of NaF on drug transport. The accelerating effect of 30mM NaF on the THP uptake by the cells had an optimum period of action (15-20min), and was concentration-dependent (5-30mM). Thirty mM potassium fluoride, as well as NaF, increased the uptake amount. On the other hand, NaF (5-30mM) dose-dependently decreased th ATP content in these cells. Additionally, the viable cells in the reaction suspension decreased by about 40% after incubation with 30mM NaF for 15min. Observing these leukocytes treated with NaF by optical microscopy, swelling of the cell and an alteration of the nuclei form occurred. On the basis of these results, we speculated that the increased THP transport in polymorphonuclear leukocytes by NaF, probably F-, might be due, at least in part, to an alteration of the morphological form.